PRAYER TIME REMINDER APPLICATION IN INDONESIA TOWN BY USING VISUAL BASIC 6.0 - Abdul Hakim; Yudi Irawan Chandra, S.Kom., MMSI (Jurnal Sistem Informasi, 2006)
In this scientific writing about the timetable set forth reminders of time of five timeobligatory prayers that are around the cities in Indonesia.With this application one can know the time schedule contained prayers throughoutthe cities in Indonesia and can be reminded directly with the call to prayer when theprayer time has come, perhaps in haste to pray without disrupting work on oneactivity. Data storage performed on the Microsoft Access database, while dataprocessing and the processing is done by programs created with Visual Basic 6.0.This application can be run on a computer that is running the operating systemWindows-based.